Differential Regulation of ABCA1 and Macrophage Cholesterol Efflux by Elaidic and Oleic Acids. Issue 8 (26th June 2013) - Shao, Fei; Ford, David A.
Abstract: Trans fatty acid consumption is associated with an increased risk of coronary heart disease. This increased risk has been attributed to decreased levels of HDL cholesterol and increased levels of LDL cholesterol. However, the mechanism by which trans fatty acid modulates cholesterol transit remains poorly defined. ATP‐binding cassette transporter A1 (ABCA1)‐mediated macrophage cholesterol efflux is the rate‐limiting step initiating apolipoprotein A‐I lipidation. In this study, elaidic acid, the most abundant trans fatty acid in partially hydrogenated vegetable oil, was shown to stabilize macrophage ABCA1 protein levels in comparison to that of its cis fatty acid isomer, oleic acid. The mechanism responsible for the disparate effects of oleic and elaidic acid on ABCA1 levels was through accelerated ABCA1 protein degradation in cells treated with oleic acid. In contrast, no apparent differences were observed in ABCA1 mRNA levels, and only minor changes were observed in Liver X receptor/Retinoic X receptor promoter activity in cells treated with elaidic and oleic acid. Efflux of both tracers and cholesterol mass revealed that elaidic acid slightly increased ABCA1‐mediated cholesterol efflux, while oleic acid led to decreased ABCA1‐mediated efflux. In conclusion, these studies show that cis and trans structural differences in 18 carbon n‐9 monoenoic fatty acids variably impact cholesterol efflux through disparate effects on ABCA1 protein degradation.